Structural Basis of TLR2/TLR1 Activation by the Synthetic Agonist Diprovocim - Su, Lijing; Wang, Ying; Wang, Junmei; Mifune, Yuto; Morin, Matthew D; Jones, Brian T; Moresco, Eva Marie Y; Boger, Dale L; Beutler, Bruce; Zhang, Hong (Journal of medicinal chemistry, 2019)
Diprovocim is a recently discovered exceptionally potent, synthetic small molecule agonist of TLR2/TLR1 and has shown significant adjuvant activity in anticancer vaccination against murine melanoma. Since Diprovocim bears no structural similarity to the canonical lipopeptide ligands of TLR2/TLR1, we investigated how Diprovocim interacts with TLR2/TLR1 through in vitro biophysical, structural, and computational approaches. We found that Diprovocim induced the formation of TLR2/TLR1 heterodimers as well as TLR2 homodimers in vitro. We determined the crystal structure of Diprovocim in a complex with a TLR2 ectodomain, which revealed, unexpectedly, two Diprovocim molecules bound to the ligand binding pocket formed between two TLR2 ectodomains. Extensive hydrophobic interactions and a hydrogen-bonding network between the protein and Diprovocim molecules are observed within the defined ligand binding pocket and likely underlie the high potency of Diprovocim. Our work shed first light into the activation mechanism of TLR2/TLR1 by a noncanonical agonist. The structural information obtained here may be exploited to manipulate TLR2/TLR1-dependent signaling.